Choice of competitive strategy of formal and informal sectors in recycling WEEE with fund subsidies: Service or price?. (20th October 2022) - Liu, Huihui; Li, Tianyou; Leong, G. Keong
Abstract: It is quite common to find that formal and informal sectors compete in the waste electrical and electronic equipment (WEEE) recycling markets in developing countries. The formal sector consists of recyclers with dismantling qualifications, while the informal sector includes recyclers without qualifications. The two sectors compete on the used products' acquisition quantities which depend on both the acquisition prices and collection services. By constructing two-stage game models, the paper studies the two sectors' competitive strategy, i.e., focusing on higher price or better service. We also examine how subsidies on the formal sector affect its decisions under two schemes of subsidies, namely, subsidy on acquisition quantity and subsidy on acquisition cost. The social welfare under two schemes of subsidies is compared under the same budget. Results show that as the collection cost of the formal sector decreases, the formal sector will adopt the service strategy by investing in its collection service, even at a cost disadvantage compared with the informal sector, while the informal sector will lower service level and raise acquisition price. A rise in subsidy level will also encourage the formal sector to use the service strategy.